PP13 Bioactive Alkaloids from Two Amaryllidaceae Species: Cytotoxic Potential Against Gastric Cancer Cells - Gonzalez Lopez, Sergio; Trujillo Chacón, Lina Marcela; Osorio Durango, Edison Javier (Revista Productos Naturales, 2025)
Cancer is a significant health problem and one of the main causes of death in the world [1]. Chemotherapy is one of the most common treatments [2], and Amaryllidaceae alkaloids represent promising cytotoxic agents and potential chemotherapeutics against various types of cancer [3;4].